Les tribulations judiciares de la mise en valeur hydroélectrique de la rivière Churchill - Gadbois, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
The Power Contract signed in 1969 between Churchill Falls (Labrador) Corporation Limited and Hydro-Québec was the result of protracted negotiations between the parties which lasted six years. It became the cornerstone of a complex financial arrangement to secure a loan which was at the time the largest private placement effected in the United States of America to provide the funds required for the construction of the Churchill Falls Plant terminated in 1976 at a cost of approximately a billion dollars. This long term contract which had led Premier Smallwood to exclaim : « Glory Hallelujah » when he had heard that the deal had been agreed upon started to be looked at in much a different light by Newfoundland following the rise in the cost of energy resulting from the increases in the price of oil demanded by OPEC. It became the nub of several Court cases instituted in the Newfoundland and Québec Courts. This article is in substance the text of a conference given by the author to the lawyers and notaries of the Ministry of Justice of Québec during the Fall of 1981. It outlines the historical events which led to the negotiations and the signing of a Letter of Intent in 1966 followed by the Power Contract in 1969 and details the events leading to the institution in September 1976 of an action before the Supreme Court of Newfoundland by the Attorney General of that province against CFLCo and Hydro-Québec for a declaration that 800 megawatts of power from Churchill Falls may be recalled, to the institution by Hydro-Québec of a declaratory action in the Québec Courts against CFLCo and the other interested parties, including the Attorney General of Newfoundland, to have certain clauses of the Power Contract interpreted and finally to the adoption in 1980 by the Newfoundland Legislature of The Upper Churchill Water Rights Reversion Act and its reference to the Court of Appeal of Newfoundland to rule on its constitutional validity.